2011
DOI: 10.1007/s11250-011-9829-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the anatomical characteristics of Peyer's patches in small intestine of Bactrian camels (Camelus bactrianus)

Abstract: The distribution, size, and appearance of Peyer's patches vary according to species. In order to determine the anatomical characteristics of Peyer's patches in small intestine of Bactrian camel, and age-related changes in the number of Peyer's patches, 40 Bactrian camels of the following four age groups were studied: young (0.5-2 years), pubertal (3-5 years), middle-aged (6-16 years), and old (17-20 years). The exact number of Peyer's patches was recorded, and the appearance of Peyer's patches was described in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Some PPs were found in the first third of the colon but they were different in shape from the scrotiform PPs observed in the ileocecal orifice. They looked very similar to the cup‐shaped or faviform PPs described previously in the ileum (Qi et al, ). The lamina propria was rich in lymphocytes, forming lymphoid follicles, the muscularis mucosa was incomplete, and the submucosa contained aggregated lymphatic nodules (Fig.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Some PPs were found in the first third of the colon but they were different in shape from the scrotiform PPs observed in the ileocecal orifice. They looked very similar to the cup‐shaped or faviform PPs described previously in the ileum (Qi et al, ). The lamina propria was rich in lymphocytes, forming lymphoid follicles, the muscularis mucosa was incomplete, and the submucosa contained aggregated lymphatic nodules (Fig.…”
Section: Resultssupporting
confidence: 83%
“…The highest number of PPs were found in the ileocecal orifice. Different forms of PPs were also observed in the mucosa of the small intestine in the Bactrian camel (Qi et al, ), but they were not as well‐developed as those in the ileocecal orifice, suggesting that the mucosal immune inductive sites in the gastrointestinal tract of the Bactrian camel are mainly located in the ileocecal orifice. Compared to the ileocecal orifice, lower numbers of PPs were present in both the middle and posterior segments in the cecum, which is in agreement with the findings in yaks and sheep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IgG ASCs density was the highest from middle segment of duodenum to middle segment of jejunum, and then in distal segment of jejunum and initial segment of ileum, the lowest was in initial segment of duodenum, in middle and distal segment of ileum. However, the results of the research on the distribution of the Bactrian camel intestinal Peyer’s patches (PPs) showed that the PPs were mainly distributed in the Ileum and there were less in the duodenum and jejunum [ 17 ]. Moreover, this distribution characteristics were similar to those in human, rat, cow and sheep’s intestine [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 6-month-old calves, the number of layers of elliptical lymphoid follicle in ileum reduced to 1 or 2 ( Figure-10 ). Only the ileal Peyer’s patch regressed to small scattered follicles in older pigs [ 24 ] and the reduction in size of ileal follicles was observed in adult dogs [ 25 ] and in Bactrian camel [ 26 ] also, after 5 years of age. Similarly in red deer, from 6 months of age, the ileal Peyer’s patch follicles began to round up, the interfollicular area in ileal Peyer’s patch also increased and resembled the morphology of the jejunal Peyer’s patch [ 17 ].…”
Section: Resultsmentioning
confidence: 99%